Thermal Energy Storage Potential of Banana Stem and Peel: Comparing Heat Conductivity at Room Temperature Post-Oven Drying - Nazarudin, Ahmad ‘Irfan; Basri, Adi Azriff; Basri, Ernnie Illyani; Ahmad, Kamarul Ariffin; Haji Hameed Sultan, Mohammed Thariq; Tamagawa, Masaaki (Journal of Advanced Research Design, 2024)
Bananas, a globally consumed staple, generate substantial agricultural waste, particularly peels and pseudostems, which account for over 60 % of the biomass. This waste presents an opportunity for value-added applications, especially in fire safety and thermal-resistant materials. In this study, dried banana pseudostems and peels were analysed for their thermal properties using Newton’s Law of Cooling. Key findings revealed that banana pseudostem outperformed the peel in thermal resistance, attributed to its higher lignin and cellulose content, which enhance insulation. These properties suggest that banana by-products hold significant potential for sustainable, thermally resistant materials, addressing fire safety challenges in regions like Malaysia. This research underscores the dual environmental and functional benefits of repurposing banana waste, aligning with sustainable development goals and promoting eco-friendly innovations.